A regulação diante de incertezas científicas: um estudo sobre a possibilidade de exploração e produção de shale gas no Brasil - Blattler, Stephanie (2018)
In Brazil, the debate regarding the exploration and production of shale gas became relevant with the 12th Bid Round promoted by the National Oil, Natural Gas and Biofuels Agency (ANP), which offered areas with great potential of such unconventional hydrocarbon. The country is listed as the tenth with greater shale gas potential in the world. However, due to the international controversy involving this energy source, mainly by virtue of its potential environmental impacts and damages, the matter was brought to the courts and is subject to legislative initiatives, so that the production of such hydrocarbon in Brazil has not started yet. Therefore, the present essay aims to clarify how the exploration and production of shale gas takes place and what would be its potential harmful effects to the environment, demonstrating that there are diverging scientific opinions over the most relevant of such effects. The description of the existing regulatory instruments in Brazil, such as ANP Resolution No. 21/2014, is also provided herein, as well as the description of the current legal proceedings and bills over the matter. Following, this essay also describes how the shale gas matter was solved in four states/countries, as to verify if there are any valuable lessons for Brazil. Based on the scientific uncertainty over the potential environmental damages and impacts, the precautionary rule is herein analyzed, aiming to understand how precaution may be applied to shale gas and to other cases under similar scientific uncertainty. Initially, the doctrine of absolute precaution is presented, followed by the main critics to precaution. Finally, the main conclusion is that the path of interpretation for the shale gas case and for other cases with similar scientific uncertainty is the use of the precautionary rule modulated by proportionality, so that its application does not reflect an immediate prohibition, but the management of uncertainties through regulation.